Einfluss des Dralls auf den Überschallnachlauf eines längsangeströmten zylindrischen Körpers - Weidner, Stephan (Schriftenreihe des Instituts fur Stromungsmechanik, Karlsruher Institut fur Technologie, 2021)
This study investigates the effects of swirl on the supersonic wake of longitudinally-aligned axisymmetric afterbodies. The swirl was introduced upstream of the base corner by either spinning non-canted or non-spinning canted fins. Depending on the introduced swirl rate, both the experimental and numerical results show two distinctively different wake flow structures. The fluid-dynamic processes present in the rotating wakes and the resulting structural changes are analyzed in detail.